2003
DOI: 10.1124/dmd.31.11.1391
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytochrome P450 Inhibition and Metabolic-Intermediate Complex Formation by Goldenseal Extract and Its Methylenedioxyphenyl Components

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The concurrent use of herbal medicinals with prescription and over-the-counter drugs carries a risk for unanticipated adverse drug-botanical pharmacokinetic interactions, particularly as a result of cytochrome P450 (P450) inhibition. Extracts of goldenseal (Hydrastis canadensis) containing approximately equal concentrations (ϳ17 mM) of two methylenedioxyphenyl alkaloids, berberine and hydrastine, inhibited with increasing potency (CYP2C9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 18 publications
2
87
1
2
Order By: Relevance
“…Evidently, the concentration of certain goldenseal components is sufficient to inactivate these enzymes in vivo. This inactivation by goldenseal likely stems from the formation of a stable heme adduct between the methylenedioxyphenyl moiety of berberine and hydrastine and the heme iron of the enzyme (Chatterjee and Franklin, 2003). Interestingly, two kavalactones, methysticin and dihydromethysticin, are also substituted methylenedioxyphenyl compounds, yet they do not inhibit CYP3A4 or CYP2D6 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the concentration of certain goldenseal components is sufficient to inactivate these enzymes in vivo. This inactivation by goldenseal likely stems from the formation of a stable heme adduct between the methylenedioxyphenyl moiety of berberine and hydrastine and the heme iron of the enzyme (Chatterjee and Franklin, 2003). Interestingly, two kavalactones, methysticin and dihydromethysticin, are also substituted methylenedioxyphenyl compounds, yet they do not inhibit CYP3A4 or CYP2D6 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches may be equally applicable to naturally occurring compounds as well as to drugs. The modeling methods could also be applied to other P450s that are known to form MIC (Chatterjee and Franklin, 2003), such as CYP3A5 and CYP2D6, enabling a comparison with the CYP3A4 data presented herein, providing insight into the features important for MIC formation, and representing a more complete picture for pharmaceutical research.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacophore, tree models, and the logistic regression model were tested with molecules outside of the training set using recently published data for 12 compounds (Yamazaki and Shimada, 1998;Kasahara et al, 2000;Kim et al, 2001;Kajita et al, 2002;Chatterjee and Franklin, 2003;Wu et al, 2003) with MIC formation for CYP3A4.…”
Section: Methodsmentioning
confidence: 99%
“…These assays allow researchers to broadly screen numerous NHP species, NHP formulations, phytochemicals, drugs, and so forth, in a high-throughput manner, thereby allowing them to target specific products to be advanced to more detailed in vitro and/or in vivo animal testing, and ultimately more informative but costly human preclinical and clinical trials. In this study, it was initially hypothesized that extracts from commercial-source goldenseal and milk thistle NHPs would be highly active in both in vitro assays because these plants are known to have constituents that are both inhibitory of CYP3A4-mediated metabolism and are substrates for P-gp transport (Budzinski et al, 2000;Maitrejean et al, 2000;Stermitz et al, 2000;Venkataramanan et al, 2000;Chatterjee & Franklin, 2003). The results of this study showed that aqueous extracts of goldenseal (NRP 17 and NRP 121) were more inhibitory of CYP3A4, with the lowest IC 50 values among all NHPs tested (ranging from 3.03 to 3.23 mg/mL).…”
Section: Discussionmentioning
confidence: 99%